Marine algae of St. Martins Island, Bangladesh. IX. New records of green algae (Chlorophyceae) (Bangladesh Journal of Plant Taxonomy, 2010)
Cladophora crispula Vickers, Cladophora prolifera (Roth) Kütz. and Phyllodictyon anastomosans (Harv.) Kraft et Wynne are recorded and described for the first time from the St. Martin’s Island, Cox's Bazar, Bangladesh.Keywords: Cladophora crispula; Cladophora prolifera; Phyllodictyon anastomosans; St. Martin’s Island.DOI: 10.3329/bjpt.v17i2.6699Bangladesh J. Plant Taxon. 17(2): 193-198, 2010 (December)